2010
DOI: 10.1007/s12264-010-1210-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical manifestations and pathophysiology of cerebral small vessel disease

Abstract: Small vessel disease (SVD) is responsible for brain chronic circular disorder, and accounts for 20%-30% cases of ischemic stroke as well as cerebral hemorrhage, and to a great extent, encephalopathy. Binswanger's disease and multiple small strokes, which are common in older people, are also closely associated with SVD. These disorders often cause decline in cognition, vascular dementia, impairment in gait and balance, mood depression, and urinary incontinence, and often brings great social and economic burdens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…All of these endothelial behaviors are important for the remodeling of matrix, ingrowth of new vessels during wound healing, and for the interaction of native endothelial cells with implanted scaffolds. Recent publications have also reported that dysregulation of the endothelium would result in the modification of the extracellular matrix (ECM) and thickness and pliability of the vascular basement membrane 4, 32–36…”
Section: Discussionmentioning
confidence: 99%
“…All of these endothelial behaviors are important for the remodeling of matrix, ingrowth of new vessels during wound healing, and for the interaction of native endothelial cells with implanted scaffolds. Recent publications have also reported that dysregulation of the endothelium would result in the modification of the extracellular matrix (ECM) and thickness and pliability of the vascular basement membrane 4, 32–36…”
Section: Discussionmentioning
confidence: 99%
“…Large (300–400 μm diameter) synthetic macrospheres induce a large lesion similar to that produced by permanent occlusion of the MCA. However, small (<50 μm) microspheres induce smaller injuries similar to the multifocal infarcts of cerebral small-vessel disease [56, 66] , which accounts for 20%–30% of cases of ischemic stroke [67] . If the spheres used are small enough to penetrate arteries, the extent of infarction and neurological deficit correlates well with the distribution and number of trapped spheres.…”
Section: Ischemic Stroke Modelsmentioning
confidence: 99%
“…Chronic cerebral hypoxic-ischemic injury, an important factor contributing to many age-related neurodegenerative disorders, 1113 also appears to involve HIF-1 related pathways. 14 Interestingly, HIF-1 activation is also reduced in aging.…”
Section: Introductionmentioning
confidence: 99%